Crop to wild gene flow and genetic diversity in a vulnerable Macadamia (Proteaceae) species in New South Wales, Australia. (November 2015) - O'Connor, Katie; Powell, Michael; Nock, Catherine; Shapcott, Alison
Abstract: Habitat fragmentation is a leading threat to biodiversity, with extinction rates increasing as anthropogenic alteration of the environment increases. Crop to wild hybridisation is a threat to biodiversity resulting from native vegetation being replaced with agriculture and crops. Remnant populations of Australia's vulnerable subtropical rainforest tree Macadamia tetraphylla are potentially threatened by hybridisation with M. integrifolia orchard crops. Leaf samples were taken from ten crop-wild population sites across the distribution of M. tetraphylla in New South Wales, Australia. Microsatellite markers were used to investigate the presence of marker alleles from cultivars in wild populations, and genetic diversity within and among wild M. tetraphylla populations. Despite the small size of the wild M. tetraphylla populations, relatively high genetic diversity and low inbreeding were observed. This study found that M. integrifolia orchard trees pollinated wild M. tetraphylla trees, and that orchard seeds dispersed into wild populations, providing the first evidence of crop-wild gene flow in macadamia. Pollen flow between relatively close wild populations maintains genetic diversity, reduces inbreeding, and also enables gene flow from nearby M. integrifolia orchards. The potential for crop to wild gene flow and hybridisation risks the integrity and persistence of wild populations.